Bomb : the race to build and steal the world's most dangerous weapon - Sheinkin, Steve (Roaring Brook Press, 2012)
Recounts the scientific discoveries that enabled atom splitting, the military intelligence operations that occurred in rival countries, and the work of brilliant scientists hidden at Los Alamos.